2002
DOI: 10.1111/j.1651-2227.2002.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high prevalence of hypercalciuria in children living in the Aral Sea region

Abstract: The Aral Sea region is a natural area seriously polluted by human activities. In addition to the increased prevalence of diverse chronic diseases in children, the risk of developing urolithiasis is reported to be high in this region. This study was undertaken to clarify the prevalence of hypercalciuria in children of the Aral Sea region. A group of 205 children living in Kazalinsk, close to the Aral Sea, and a group of 187 children living in Zhanakorgan, far from the Aral Sea, were screened for hypercalciuria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The population living in the Aral Sea area faces numerous health issues, with high rates of anemia, cancers, respiratory illness, and birth defects being among the most commonly reported health problems (Kaneko et al 2002; Ataniyazova et al 2001; Giebel et al 1998; Hashizume et al 2003; Kunii et al 2003; Zaridze et al 1992; Crighton et al 2003b). These conditions have been linked either directly or indirectly to the areas environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The population living in the Aral Sea area faces numerous health issues, with high rates of anemia, cancers, respiratory illness, and birth defects being among the most commonly reported health problems (Kaneko et al 2002; Ataniyazova et al 2001; Giebel et al 1998; Hashizume et al 2003; Kunii et al 2003; Zaridze et al 1992; Crighton et al 2003b). These conditions have been linked either directly or indirectly to the areas environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The increased dust storms in the Aral Sea area, particularly in the southwestern region of Uzbekistan, represent a challenge impacting human health (Groll et al 2013). Some authors report that the worsening ecological situation in the Aral Sea zone has led to a prevalence of anemia and restrictive pulmonary dysfunction, as well as a high risk of developing urolithiasis in adults and increased infant mortality (Kaneko et al 2002;Kunii et al 2003;Crighton et al 2011;Groll et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is may be secondary to low creatinine excretion per unit body mass [8] and also tubular immaturity to excrete creatinine [11]. If sex factor is considered, as previous reports it was found that there was no significant difference in urinary Ca/Cr ratio between both sex [9,13,19,22]. As for most analytes, the lower and upper reference limits are assumed to demarcate the estimated 2.5 th and 97.5 th percentiles respectively, of the underlying distribution of values [24], percentile values of urinary Ca/Cr ratio were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…It is incumbent on a laboratory to report urinary Ca/Cr ratio, and a reference interval must be required above which a result is considered abnormal, but these cut-offs are not firmly established because of difficulties of generating reference intervals for children particularly across the span of ages in childhood [11]. Reference values for urine calcium/ creatinine ratio in normal infant and children have been reported by several authors worldwide, but these data are controversial, possibly due to the differences between study populations, genetic characteristics and the variations in dietary intake of calcium, sodium and protein in different geographic regions [1][2][3][4]9,10,[12][13][14][15]. So the objective of the present study was to determine urine Ca/Cr ratio in healthy infant and children in Burdwan district, West Bengal.…”
Section: Introductionmentioning
confidence: 98%